2021
DOI: 10.1515/ijnes-2020-0109
|View full text |Cite
|
Sign up to set email alerts
|

Nursing student and faculty attitudes about a potential genomics-informed undergraduate curriculum

Abstract: Objectives To explore attitudes about adding genomic content to an undergraduate nursing curriculum. Genomic knowledge is essential to nursing education, but challenges exist for curriculum innovation. Few countries have guiding documents from national nursing organizations on genomic competencies for practice or education. Information on attitudes about genomics may provide guidance for curriculum development. Methods Ninete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…With this in mind, leaders can use early adopters to create shifts in acceptance and interest in knowledge integration. Rogers' ( 2003) theory was successfully used in this way to advance nursing practice in genomics (Andrews et al 2014;Dewell et al 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With this in mind, leaders can use early adopters to create shifts in acceptance and interest in knowledge integration. Rogers' ( 2003) theory was successfully used in this way to advance nursing practice in genomics (Andrews et al 2014;Dewell et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Role clarity in genomics-informed nursing care was raised as an issue in Canada (Bottorff et al 2005a;Dewell et al 2021) and is identified as a key enabler for professional practice (Tonkin et al 2020a). Role clarity has challenged nurses for decades (Almost 2021).…”
Section: Clarify Nurses' Unique and Overlapping Role In Genomics To I...mentioning
confidence: 99%
“…The lack of faculty confidence in genomic content in this study is a commonly reported barrier to advancing nursing genomic knowledge (Read & Ward, 2018). In a recent qualitative study exploring attitudes regarding adding genomic content to an undergraduate nursing curriculum, faculty and students acknowledged important gaps in understanding genomic constructs and reported that they were not applying information to their current nursing educational setting even when they took a previous genomic course (Dewell et al, 2021). Both faculty and students recognized clinical and didactic opportunities where genomic content could be applied.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic knowledge among nursing needs to be explored to determine competency in the current environment where genetics is informing health care (Anderson et al, 2015). As previously highlighted, practicing nurses and nursing students and faculty lack basic knowledge about foundational genomic content, and a major barrier to genomic nursing education is inadequate faculty preparation in genomic subject matter (Dewell et al, 2020, 2021; Read & Ward, 2016); however, less is known about the genomic competency and knowledge of advanced practice nursing students and their faculty. This study aims to examine the genomic competency of advanced practice registered nursing students and faculty in a graduate school of nursing.…”
Section: Problem and Significance To Nursingmentioning
confidence: 99%
See 1 more Smart Citation